A case of ectopic hamartomatous thymoma: controversy over the designation - Makio Hayama; Seiji Yoshitomi; Maiko Tamura; Nobuhiko Ohnishi; Shigeharu Moriyama (Surgical Case Reports, 2019)
Abstract Background Ectopic hamartomatous thymoma, which usually occurs in the lower neck, is a rare benign tumor containing spindle cells, epithelial nests, and adipose tissue. Although the origin of this tumor is still unknown, recent reports suggest that the designation of this tumor is inappropriate. Case presentation A 38-year-old with an anterior cervical mass in the suprasternal region of her neck was referred to our hospital. An ultrasound examination showed that the well-defined oval mass was 31 × 23 × 17 mm in size. A non-enhanced computed tomography scan of the neck revealed that the distinct neck mass in the subcutaneous tissue had a mixture of soft tissue and fatty components. The cervical tumor was clinically diagnosed to be an unusual lipoma with degeneration. The patient underwent the neck mass extirpation. During the surgery, the cervical mass was well demarcated and did not adhere to the surrounding tissues. The postoperative course was uneventful. The gross pathology report showed that the neck mass measured 3.0 × 2.5 × 2.0 cm. Microscopically, the tumor was composed of spindle cells, epithelial nests, and mature adipose tissue. Immunohistochemical examination revealed that both spindle cells and epithelial nests were positive for cytokeratin AE1/AE3. These histopathological findings were consistent with the features of ectopic hamartomatous thymoma. Over a follow-up period of 30 months, this patient exhibited no evidence of recurrence. Conclusions Ectopic hamartomatous thymoma should be considered in the differential diagnosis of subcutaneous tumors in the lower neck, when the CT shows the tumor has the mixed components of fat and soft tissues.